2005
DOI: 10.1359/jbmr.050112
|View full text |Cite
|
Sign up to set email alerts
|

Serum Retinoids and β-Carotene as Predictors of Hip and Other Fractures in Elderly Women

Abstract: There is debate about the possible deleterious effect of excessive vitamin A exposure on fracture risk. In this nested case control study in older women (312 cases and 934 controls), serum retinol, retinyl palmitate, and ␤-carotene were not associated with fracture risk, and there was no evidence of excess risk with multivitamin or cod liver oil supplementation.Introduction: Recent studies have suggested that higher vitamin A intake may account for a component of fracture risk within the general population and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 30 publications
2
84
3
2
Order By: Relevance
“…These studies have yielded a range of different results with some identifying an association between poor bone health and either low serum retinol (42)(43)(44)(45) or excess vitamin A (4-10, 46), or no difference between study groups (47)(48)(49)(50)(51)(52)(53)(54)(55)(56). For a detailed review see Conaway et al (57).…”
Section: A Number Of Cross Sectional and Longitudinal Studies Have Asmentioning
confidence: 99%
“…These studies have yielded a range of different results with some identifying an association between poor bone health and either low serum retinol (42)(43)(44)(45) or excess vitamin A (4-10, 46), or no difference between study groups (47)(48)(49)(50)(51)(52)(53)(54)(55)(56). For a detailed review see Conaway et al (57).…”
Section: A Number Of Cross Sectional and Longitudinal Studies Have Asmentioning
confidence: 99%
“…Studies have also reported an association between high intake of vitamin A and reduced bone mineral density (BMD) (2,5,6). However, several studies have also failed to establish a relationship between serum concentrations of retinol, vitamin A supplementation, and bone density (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Lower serum lycopene, cryptoxanthin, and beta-carotene concentrations have been associated with lower BMD [59,60]. In other studies, foods containing higher amounts of carotenoids have been associated with higher BMD [61,62]. In one study, higher total carotenoids and lycopene intakes were associated with reduced fracture incidence in women and men [63].…”
Section: Carotenoidsmentioning
confidence: 89%